An Inclusive Vocational and Technical School at Sokwai, Ashanti Region - Tettey, Nunya Yao (2011)
A Thesis submitted to the Department of Architecture, Kwame Nkrumah University of Science and Technology in Partial Fulfillment for the Degree of MASTER OF ARCHITECTURE.